Analisis Nilai Tambah Asinan Rebung Bambu Tabah (Gigantochloaa nigrociliata Burze-Kurz) Berdasarkan Nilai Organoleptik Terbaik Selama Fermentasi - Howbert, Randall; Antara, Nyoman Semadi; Wijaya, I Made Mahaputra (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): Desember, 2019)
The purpose of this study is to determine the added value of the processed bamboo shoots pickle at the optimum fermentation time. The study was divided into 3 stages, the first stage were determining the best organoleptic properties during fermentation, secondly analyzing the characteristics of bamboo shoots pickles at determined optimum fermentation time, and lastly analyzing the added value of processing the bamboo shoots turned to pickles. The results showed that the most preferred organoleptic value of bamboo shoots pickles was fermentation on day 4 with the hedonic score of 5.65 (slightly preferred  ? preferred) with chemical and microbiological characteristics of bamboo shoots and its liquids microbial population 4.6 x 10 7 CFU/ml and 8.4 x 10 7   CFU/ml, and lactic acid levels of 0.56% and 0.63%, with salinity of 2.89% and 3.51%, pH 4.0 and 3.7 and reduced sugar content of 1.87% and 2.70%. The value added analysis showed that in a year scenario the producing of bamboo shoots to become pickled using raw materials as much as 566.4 Kg could produce 1510.4 Kg of bamboo shoots pickles (320 gram/jar), of which the results obtained an added value of IDR 566.984.936/ year with added value ratios amounting to 87.89% and the profit received by the company is IDR. 554.273.072 (92.09%). Keyword : Gigantochloaa nigrociliata Burze-Kurz, bamboo shoot pickle, fermentation, organoleptic, added value.